DO INTERNATIONAL NESB STUDENTS NEED AN ACADEMIC LANGUAGE DEVELOPMENT PROGRAM? - Bambang Yudi Cahyono (Soegijapranata Catholic University, 2004)
This study examined the academic language skills of international students from non-English speaking background (NESB) at the University of Melbourne. It aimed to determine whether or not they need an academic language development program. The participants were 158 international NESB students of distinct categories. The students' academic language were measured using the Diagnostic English Language Assessment (DELA) test administered before the commencement of their academic study. Scores of the test were compared across categories and correlated across academic language skills. The results from this study suggested that. in general. international NESB students need a language development program to improve their academic writing skill. In addition. it was suggested that the development of the academic writing skill of international N ESB students be accomplished through a program directly related to academic language writing.